Protective Efficacy of a Mucosal Influenza Vaccine Formulation Based on the Recombinant Nucleoprotein Co-Administered with a TLR2/6 Agonist BPPcysMPEG - Sanchez Sanchez, Maria Victoria (2023)
Current influenza vaccines target highly variable surface glycoproteins; thus, mismatchesbetween vaccine strains and circulating strains often diminish vaccine protection. For this reason,there is still a critical need to develop effective influenza vaccines able to protect also against thedrift and shift of different variants of influenza viruses. It has been demonstrated that influenzanucleoprotein (NP) is a strong candidate for a universal vaccine, which contributes to providingcross-protection in animal models. In this study, we developed an adjuvanted mucosal vaccine usingthe recombinant NP (rNP) and the TLR2/6 agonist S-[2,3-bispalmitoyiloxy-(2R)-propyl]-R-cysteinylamido-monomethoxyl-poly-ethylene-glycol (BPPcysMPEG). The vaccine efficacy was compared withthat observed following parenteral vaccination of mice with the same formulation. Mice vaccinatedwith 2 doses of rNP alone or co-administered with BPPcysMPEG by the intranasal (i.n.) route showedenhanced antigen-specific humoral and cellular responses. Moreover, NP-specific humoral immuneresponses, characterized by significant NP-specific IgG and IgG subclass titers in sera and NP-specificIgA titers in mucosal territories, were remarkably increased in mice vaccinated with the adjuvantedformulation as compared with those of the non-adjuvanted vaccination group. The addition ofBPPcysMPEG also improved NP-specific cellular responses in vaccinated mice, characterized byrobust lymphoproliferation and mixed Th1/Th2/Th17 immune profiles. Finally, it is notable thatthe immune responses elicited by the novel formulation administered by the i.n. route were able toconfer protection against the influenza H1N1 A/Puerto Rico/8/1934 virus.